Article Commentary: SARS-CoV-2 and HIV Protease Inhibitors: Why Lopinavir/Ritonavir will not Work for COVID-19 Infection. Issue 7 (October 2020) - Smolders, Elise J; te Brake, Lindsey HM; Burger, David M
Since the beginning of the outbreak of severe acute respiratory syndrome (SARS) coronavirus (CoV) 2, lopinavir/ritonavir was selected for treatment. The recent publication of Cao et al . in the New England Journal of Medicine showed that lopinavir/ritonavir treatment did not accelerate clinical improvement compared with standard of care. This raised the question of whether in retrospect we could have known this. The aim of this paper is to gather all the available evidence and to comprehensively discuss this issue.